Multiplexity in Civilization Studies: Insights from Ibn Khaldun and Said Halim Pash - Miftah, Mukerrem (İbn Haldun Çalışmaları Dergisi, 2018)
The study of civilization has always been approached from various perspectives. A closer appraisal of some of these pursuits reveals at least three major trends, especially in the contexts of Islamic and Western civilizations. The first trend employs more of a “historio-empirical” approach; the second emphasizes a “religiophilosophical” approach; and finally, the last trend adopts more of a “multiplex” approach to the study of civilizations. Whilst the first two trends are equally applicable to Islamic and western civilizations, the “Multiplex” trend is arguably more pronounced in the study of Islamic civilization. The paper argues that “Multiplexity”, subsuming multiplicity and complexity on methodological terms, is best represented by the works of Ibn Khaldun and Said Halim Pasha. This approach to civilization studies, among other things, challenges reductionism both on methodological as well as epistemological grounds. Compared to the other two, it gives due attention to multiple factors, such as economic, political, cultural, religious, historical, philosophical and physical factors, and the interlocking intricacies among them in an effort to account for the phenomenon of civilization. It can, therefore, present an alternative, but more holistic, approach to civilization studies, and in that, it transcends the impasse posed by historical, economic, physical, racial, religious and other determinisms and reductionisms.